Minority Women, Rights and Intersectionality (Taylor & Francis, 2025)
This collection focuses on minority women through the perspectives of minority rights and intersectionality to investigate key concepts such as discrimination, inequality, agency, participation, resistance, and solidarity while also unpacking dynamics of power. It presents diverse grounded empirical cases drawing on field research and data collection while offering a global perspective that explores intersectionality and its effects on minority women ascribed alternately by nationality, religion, ethno-culture, gender, migration background, and race in seven countries as well as in digital and international political spaces. The authors include legal scholars, political scientists, sociologists, and anthropologists who study inequality, minority rights, race and gender issues, and the digital sphere. This interdisciplinary concatenation of authors offers an advantage when working at the junction between intersectionality and minority rights. Interdisciplinary in approach, the book will be of interest to researchers, academics, and policy-makers working in the areas of Human Rights Law, Minority Rights, Gender Studies, Political Science, Social and Cultural Anthropology, and Sociology. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution (CC-BY)] 4.0 license.